Bladder tumor ILC1s undergo Th17‐like differentiation in human bladder cancer. (8th September 2021) - Mukherjee, Neelam; Ji, Niannian; Tan, Xi; Lin, Chun‐Lin; Rios, Emily; Chen, Chun‐Liang; Huang, Tim; Svatek, Robert S.
Abstract: Purpose: Human innate lymphoid cells (hILCs) are lineage‐negative immune cells that do not express rearranged adaptive antigen receptors. Natural killer (NK) cells are hILCs that contribute to cancer defense. The role of non‐NK hILCs in cancer is unclear. Our study aimed to characterize non‐NK hILCs in bladder cancer. Experimental design: Mass cytometry was used to characterize intratumoral non‐NK hILCs based on 35 parameters, including receptors, cytokines, and transcription factors from 21 muscle‐invasive bladder tumors. Model‐based clustering was performed on t‐distributed stochastic neighbor embedding (t‐SNE) coordinates of hILCs, and the association of hILCs with tumor stage was analyzed. Results: Most frequent among intratumoral non‐NK hILCs were hILC1s, which were increased in higher compared with lower stage tumors. Intratumoral hILC1s were marked by Th17‐like phenotype with high RORγt, IL‐17, and IL‐22 compared to Th1 differentiation markers, including Tbet, perforin, and IFN‐γ. Compared with intratumoral hILC2s and hILC3s, hILC1s also had lower expression of activation markers (NKp30, NKp46, and CD69) and increased expression of exhaustion molecules (PD‐1 and Tim3). Unsupervised clustering identified nine clusters of bladder hILCs, which were not defined by the primary hILC subtypes 1–3. hILC1s featured in all the nine clusters indicating that intratumoral hILC1s displayed the highest phenotypic heterogeneity among all hILCs. Conclusions: hILC1s are increased in higher stage tumors among patients with muscle‐invasive bladder cancer. These intratumoral hILC1s exhibit an exhausted phenotype and Th17‐like differentiation, identifying them as potential targets for immunotherapy. Abstract : This study characterizes the diversity of tumor‐infiltrating ILCs within muscle‐invasive bladder cancer. Unique ILC subtypes were identified that differed from traditional classifications of ILCs. We further found that bladder ILC1s displayed a Th17‐like phenotype and correlated with tumor stage, suggesting further investigations into their role in cancer and potential immunotherapy targets.